Redescription of Minosiella intermedia Denis, 1958 (Araneae: Gnaphosidae) withfirst description of the male - Marusik, Yuri M.; Kovblyuk, Mykola M. (Zootaxa, 2009)
Minosiella Dalmas, 1921 is a small genus of Gnaphosinae spiders comprising only six species known from western Palaearctic, ranging from Algeria to Afghanistan (Platnick, 2009). Males of this genus can be easily recognized thanks to strong cymbial spines (Figs 1–3, 9–11). Four species of Minosiella are known from both sexes, and two from females only. One of the latter, Minosiella intermedia Denis, 1958 was reported from Turkmenistan and from the Aral Sea (Ovtsharenko & Fet, 1980; Krivokhatski & Fet, 1982; Mikhailov, 1997). Although this species was reported several times from the former Soviet Union and not less than 450 specimens of M. intermedia have been collected in Karakum Desert (Krivokhatski & Fet, 1982), the male of this species was not described yet.